Understanding participatory budgeting through formal and informal processes of inclusion: a case study in the Philippines. Issue 4 (18th May 2020) - Maravilla, Gladys Ann R.; Grayman, Jesse Hession
ABSTRACT: From 2012 to 2017, the Philippines' bottom-up budgeting (BUB) programme was a government initiative that leveraged participation to ensure the public were involved in crafting their own development programmes. This article advances notions of formal and informal spheres of participation to understand how the BUB empowered people by taking part in various participatory processes. The case study shows how participation is inherently political, but it cannot be disregarded as a potent tool for exercising democracy. The article highlights the potential of participatory practices in popular and informal spaces without abandoning the formal spheres of participation.